A comparative study of ultrasound-guided caudal block versus anatomical landmark-based caudal block in pediatric patients undergoing infra-umbilical surgeries - Suman Halder; Amrita Roy; Payel Mitra; Maitreyee Mukherjee; Arpita Laha (Asian Journal of Medical Sciences, 2025)
Background: Pain is an unpleasant sensory and emotional experience that can lead to a variety of potentially negative sequelae in any age group. Thus, efficient and optimum pain management is essential. Optimum post-operative pain management is crucial for preventing adverse sequelae in the post-operative period. Caudal epidural block is a commonly performed regional anesthetic technique for maintaining intra- and post-operative analgesia for pediatric patients undergoing lower abdominal, urogenital, and lower limb surgeries. Aims and Objectives: This study was done to compare the success rate and complications between ultrasound (USG) and landmark-guided caudal epidural analgesia in infra-umbilical surgeries in children aged more than 1 month–<12 years. Materials and Methods: A total of 150 subjects were randomly allocated into two equal groups (each of 75 patients). Double blinding was done. Both the groups were compared for procedural time, occurrences of subcutaneous swelling, hemorrhagic tap, dural puncture, requirement of intraoperative fentanyl as rescue analgesia, and post-operative analgesia by revised Face, Legs, Activity, Cry, Consolability and Visual Analog Scale score. Results: USG-guided caudal block had significantly higher (P<0.001) procedure time (mean±standard deviation procedure time=11.6±1.6), significantly lower (P=0.003) incidence of subcutaneous swelling, and significantly lower (P=0.012) requirement of fentanyl. Post-operative pain was comparable. Conclusion: USG-guided caudal block was more time-consuming (P<0.001) but with a higher success rate and subcutaneous swelling (P=0.003) occurred less.